2019
DOI: 10.1002/aic.16694
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of local bubble properties: Comparison to the sectional quadrature method of moments

Abstract: In recent years, population balance models coupled to computational fluid dynamics have been used as a tool to model bubbly flows. In this work, we established a setup to measure the local size distribution, the velocity and orientation of bubbles in different zones of a bubble column. As a population balance model, we used the sectional quadrature method of moments for the first time in OpenFOAM to simulate the local change in the bubble size distribution and compared its results to the quadrature method of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Section-wise approximation with QMOM. Attarakih et al [100] Schäfer et al [101] One-group models One primary one secondary particle method (OPOSPM)…”
Section: Marchisio and Fox [94]mentioning
confidence: 99%
“…Section-wise approximation with QMOM. Attarakih et al [100] Schäfer et al [101] One-group models One primary one secondary particle method (OPOSPM)…”
Section: Marchisio and Fox [94]mentioning
confidence: 99%
“…Also, the SQMOM recently found application in bubble column flows. Schäfer et al [323] implemented the SQMOM in OpenFOAM ® . The outcomes of numerical simulations have been validated with experiments, showing good agreement in terms of the time-averaged vertical component of the velocity, instantaneous velocity field of the disperse phase, and the shape of BSD in general.…”
Section: Pbe Discretization Methodsmentioning
confidence: 99%
“…Attarakih et al [121] provided further details, including implementation; they also suggested to use a low number of secondary particles for improved conditioning of the moment inversion and to increase accuracy by using a larger number of primary particles. SQMoM has been applied in combination with CFD modeling of liquid extraction columns [122][123][124][125] and bubble columns [74,126].…”
Section: Sectional Quadrature Methods Of Moments (Sqmom)mentioning
confidence: 99%